2005
DOI: 10.1631/jzus.2005.b0307
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of nitrate and heavy metals by iron metal

Abstract: Great attention should be paid now to simultaneously removing common pollutants, especially inorganic pollutants such as nitrate and heavy metals, as individual removal has been investigated extensively. Removing common pollutants simultaneously by iron metal is a very effective alternative method. Near neutral pH, heavy metals, such as copper and nickel, can be removed rapidly by iron metal, while nitrate removal very much slower than that of copper and nickel, and copper can accelerate nitrate removal when b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…This hypothesis is supported by previous studies, which showed that Ni was mainly scavenged by Fe oxyhydroxides (e.g. Xu et al, 2007;Gunsinger et al, 2006;Sterckeman et al, 2006;Dries et al, 2005;Hao et al, 2005;Stipp et al, 2002;Li et al, 2000). Nachtegaal and Sparks (2002) noted that this phenomenon was enhanced by the presence of humic acids.…”
Section: Tephra As An Active Barrier -The Case Of H3 Tephrasupporting
confidence: 80%
“…This hypothesis is supported by previous studies, which showed that Ni was mainly scavenged by Fe oxyhydroxides (e.g. Xu et al, 2007;Gunsinger et al, 2006;Sterckeman et al, 2006;Dries et al, 2005;Hao et al, 2005;Stipp et al, 2002;Li et al, 2000). Nachtegaal and Sparks (2002) noted that this phenomenon was enhanced by the presence of humic acids.…”
Section: Tephra As An Active Barrier -The Case Of H3 Tephrasupporting
confidence: 80%
“…In particular, at pH values that are relevant to natural systems, iron readily precipitates and the adsorptive affinity of the oxide-film for cations is increased (pH > pH pzc ). Therefore, it is surprising that adsorption and co-precipitation has received less attention in the discussion results of cation removal by Fe 0 /H 2 O systems [43,44]. Hao et al [44] reported that Cu 2+ enhances nitrate reduction by Fe 0 .…”
Section: Fe 0 -Based Alloys In Hydrometallurgymentioning
confidence: 99%
“…Therefore, it is surprising that adsorption and co-precipitation has received less attention in the discussion results of cation removal by Fe 0 /H 2 O systems [43,44]. Hao et al [44] reported that Cu 2+ enhances nitrate reduction by Fe 0 . Even though this is possible through an indirect reaction, "NO 3 − removal" and "NO 3 − reduction" are not randomly interchangeable without precise investigations.…”
Section: Fe 0 -Based Alloys In Hydrometallurgymentioning
confidence: 99%
“…Zero-valent metal (Fe 0 , Al 0 ) will remove [5,38,40] nitrates [41][42][43][44][45][46][47][48][49][50][51][52][53][54], nitrites [55,56], bromates [54], chlorates [54], organic compounds (including organo-halides [4][5][6][7]16,[57][58][59][60][61][62][63]) and metals (Ag [64], Al [5], As [40,65,66], Ba [5], Cd [12,64], Co [40], Cr [5,63], Cu [5,42], Fe [5], Hg [64], Mn [5], Ni [42], Pb …”
Section: Space Velocitymentioning
confidence: 99%
“…Adding Al salts to Fe 0 increases the rate of organic contaminant removal [38,70,71]. Adding Cu 0 to Fe 0 increases the rate of metal and nitrate contaminant removal [42]. Following n-ZVM injection/infiltration Eh and pH change progressively with time [6], i.e., the water composition is a function of space velocity, SV (m 3 H 2 O h −1 t −1 ZVM).…”
Section: Space Velocitymentioning
confidence: 99%